A first look at childhood abuse in women with obstructive sleep apnea - Pal, Amrita; Martinez, Fernando; Wagman, Jennifer; Aysola, Ravi S.; Shechter, Ari; Mysliwiec, Vincent; Martin, Jennifer L.; Macey, Paul M. (Frontiers in Sleep, 2024)
Study objectives. Women who experienced childhood sexual abuse have higher rates of obesity, a risk factor for obstructive sleep apnea (OSA). We assessed if prior childhood sexual abuse was more common in women with OSA vs. control, with possible mediation by obesity.In a secondary analysis of a larger project, we studied 21 women with OSA (age mean±s.d. 59±12 years, body mass index (BMI) 33±8 kg/m 2 , respiratory event index [REI] 25±16 events/hour, Epworth Sleepiness Scale [ESS] 8±5) and 21 women without OSA (age 53±9 years, BMI 25±5 kg/m 2 , REI (in 7/21 women) 1±1 events/hour, ESS 5±3). We evaluated four categories of trauma (general, physical, emotional, and sexual abuse) with the early trauma inventory self report-short form (ETISR-SF). We assessed group differences in trauma scores with independent samples t-tests and multiple regressions. Parametric Sobel tests were used to model BMI as a mediator for individual trauma scores predicting OSA in women.Early childhood sexual abuse reported on the ETISR-SF was 2.4 times more common in women with vs. without OSA (p=0.02 for group difference). Other trauma scores were not significantly different between women with and without OSA. However, BMI was a significant mediator (p=0.02) in predicting OSA in women who experienced childhood physical abuse.Conclusions. Childhood sexual abuse was more common in women with versus without OSA.BMI was a mediator for OSA of childhood physical but not sexual abuse. This preliminary hypothesis-generating study suggests there may be physiological impacts of childhood trauma in women that predispose them to OSA.